Dynamics of Chinese Comparative Advantage - Jeroen Hinloopen; Charles van Marrewijk (Tinbergen Institute, 2004)
We analyze the dynamics of Chinese comparative advantage as measured by export shares and the Balassa index using 3-digit and 4-digit sectors for the period 1970 – 1997. We use novel tools to identify periods of rapid structural change and the persistence of comparative advantage, such as Galtonian regressions, probability-probability (p-p) plots, and the Harmonic Mass index, to supplement the usual descriptive statistical methods and mobility indicators associated with Markov transition matrices.
Keywords: E63; F14; F40; N95; O10; O53; P30; R11; 330; Balassa index; distribution dynamics; Galtonian regression; Markov matrices; P-P plots; HM index; Komparativer Vorteil; China